2020
DOI: 10.1007/s12471-020-01442-w
|View full text |Cite
|
Sign up to set email alerts
|

The 2010s in clinical drug-eluting stent and bioresorbable scaffold research: a Dutch perspective

Abstract: Dutch researchers were among the first to perform clinical studies in bare metal coronary stents, the use of which was initially limited by a high incidence of in-stent restenosis. This problem was greatly solved by the introduction of drug-eluting stents (DES). Nevertheless, enthusiasm about firstgeneration DES was subdued by discussions about a higher risk of very-late stent thrombosis and mortality, which stimulated the development, refinement, and rapid adoption of new DES with more biocompatible durable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Regarding the incorporated drugs, new substances have been proposed in these stents, such as zotarolimus, everolimus, and novolimus [ 6 , 68 , 69 , 70 , 71 , 72 ]. Through their diffusion into the vessel wall, these compounds lead to good endothelial coverage, inhibition of vascular restenosis, and suppression of transplant rejection [ 20 , 22 , 52 , 63 ].…”
Section: Evolution Of Cardiovascular Stentsmentioning
confidence: 99%
“…Regarding the incorporated drugs, new substances have been proposed in these stents, such as zotarolimus, everolimus, and novolimus [ 6 , 68 , 69 , 70 , 71 , 72 ]. Through their diffusion into the vessel wall, these compounds lead to good endothelial coverage, inhibition of vascular restenosis, and suppression of transplant rejection [ 20 , 22 , 52 , 63 ].…”
Section: Evolution Of Cardiovascular Stentsmentioning
confidence: 99%
“…In current clinical practice in the Netherlands and Belgium, discriminating stent use is highly unlikely, as DES implantation is the standard of care and new-generation DES are widely available [ 20 , 21 ]. Likewise, in our present study, trial participants of all ethnic backgrounds were treated with randomly allocated new-generation DES, which precludes any stent choice.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested an increased adverse event risk in ethnic minority patients as compared to non-immigrants [7,13]. Meanwhile, there has been substantial progress in DES design, PCI techniques, and concomitant medication [20,21].…”
Section: Clinical Outcome Of Ethnic Minority Patients With Different ...mentioning
confidence: 99%
“…Although more invasive CABG is superior in some groups of patients, they have become the preferred methods of revascularization (4)(5)(6). On the other hand, reocclusion of the coronary arteries due to thrombotic occlusion in acute stages or neointimal hyperplasia (NIH) in the longer periods following minimally invasive techniques has been a major problem after MIT, particularly after bare metal stents (BMS) (7)(8)(9). In the longer period re-occlusion process, multiple factors such as smooth muscle cell (SMC) migration, activation of some cytokines and growth factors, extracellular matrix formation, neutrophil/macrophage activation are involved.…”
Section: Introductionmentioning
confidence: 99%